2019
DOI: 10.1111/cote.12402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pigment colour on the printing performance of synthetic leather using a ultraviolet‐curable water‐borne polyurethane acrylate binder

Abstract: The effect of pigment colours, cyan (C), magenta (M) and yellow (Y), and a blend of these (CMY blend) on the printing performance of synthetic leather using a ultraviolet (UV)‐curable water‐borne polyurethane acrylate binder and two types of photoinitiators was investigated. The curing process was carried out at different radiation doses using gallium and mercury UV lamps in combination. The performance of the prints was evaluated with abrasion resistance, crock fastness, gloss and hardness values and K/S. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The properties of PU, including the hardness and softness, can be tailored by adjusting the quantities and types of isocyanates and polyols used in the synthesis process. In addition, the final material can be modified by incorporating additives such as flame retardants, 61 moisture scavengers, 62 surfactants, 63 pigments, 64 and blowing agents. 65…”
Section: Polyurethane Synthesismentioning
confidence: 99%
“…The properties of PU, including the hardness and softness, can be tailored by adjusting the quantities and types of isocyanates and polyols used in the synthesis process. In addition, the final material can be modified by incorporating additives such as flame retardants, 61 moisture scavengers, 62 surfactants, 63 pigments, 64 and blowing agents. 65…”
Section: Polyurethane Synthesismentioning
confidence: 99%
“…Studies of UV-cured acrylates have reported that curing occurs via the decrease and disappearance of the vibration peaks of the C=C double bonds. The absorption peaks of vibration of the C=C double bond appear at 810, 840, and 950 cm‫,¹-‬ stretching over the range of 1410 to 1420 cm‫¹-‬ [26,3435]. In Figure 3, the decrease and disappearance of the twisting peak at 810 cm‫¹-‬ and the stretching peak at 1410 cm‫¹-‬ reveal that polymerization occurred after the UV-curing process.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 95%
“…The cured ink film was analyzed to confirm the occurrence of UV-curing as the decrease and disappearance of the twisting peak at 810 cm‫,¹-‬ and a stretching peak at 1410 cm‫¹-‬ represented the polymerization that occurred after the UV-curing process [25,26,34]. The UVcurable ink was printed and cured on 2-mm acrylic plates in pale blue PANTONE P115-4C…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used in leather, paper, adhesives, coatings and other aspects. [1][2][3][4] In recent years, WPUA materials have developed in a multifunctional trend. Many researchers have improved the performance of WPUA by adjusting the ratio of raw materials or by introducing new substances.…”
Section: Introductionmentioning
confidence: 99%